2011
DOI: 10.1001/archoto.2011.32
|View full text |Cite
|
Sign up to set email alerts
|

Patient Adjustment to Reduced Olfactory Function

Abstract: These scores suggest adjustment processes in the daily use of the sense of smell by patients. Patients attach less importance to their current sense of smell in daily life than do normosmic individuals. This adjustment might be an example of regaining psychological health despite acquired and long-lasting impairments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 24 publications
4
31
1
Order By: Relevance
“…Olfactory evaluation, however, is not common in routine health assessments. From our findings, clinicians could ask current and perceived changes in smell and flavor to identify severe olfactory dysfunction and could follow up with additional assessments (Croy et al 2011; Pusswald et al 2012) and evaluation if the dysfunction interferes with health, nutritional status, and/or well-being (quality of life). There are many qualitative aspects of smell impairments, such as presence of phantom or distorted smells, which are not captured by routine olfactory testing.…”
Section: Discussionmentioning
confidence: 99%
“…Olfactory evaluation, however, is not common in routine health assessments. From our findings, clinicians could ask current and perceived changes in smell and flavor to identify severe olfactory dysfunction and could follow up with additional assessments (Croy et al 2011; Pusswald et al 2012) and evaluation if the dysfunction interferes with health, nutritional status, and/or well-being (quality of life). There are many qualitative aspects of smell impairments, such as presence of phantom or distorted smells, which are not captured by routine olfactory testing.…”
Section: Discussionmentioning
confidence: 99%
“…Usually patients with olfactory loss attach less importance to their current sense of smell in daily life than do individuals with normal olfactory function. 22 Although these individuals adapt, the scope of olfactory sensing is restricted by the degree of olfactory loss. We thought that this restricted olfactory scope is the reason why BDI scores were inversely correlated with TDI scores There was a statistically significant correlation.…”
Section: Discussionmentioning
confidence: 99%
“…Neuland et al 36 found that patients with congenital anosmia indicated no loss (0%) in QoL, while acquired hyposmia affected QoL more than acquired anosmia. Croy et al 37 reported that patients with OD duration of more than 1 year tended to use their sense of olfaction less often than patients with shorter disorder duration, indicating adjustment.…”
Section: Instrument For Qol Evaluation In Patients With Odmentioning
confidence: 99%